Research On Android Intelligent Phones Controlling the Car to Run - Jinsong Song; Zhenghua Xin; Wei Ding (Institute of Advanced Engineering and Science, 2013)
The system finished the android smart mobile phone to control the intelligent car to avoid the obstacles wirelessly based on the bluetooth communication protocol. The android system is popular. But researches on applying it in the wireless sensors are very few. This paper allowed the bluetooth-enabled android phones to communicate with sensors wirelessly through our designed software. The software is installed simplely on the phones.The operator can run the software and touch the screen on the intelligent phones to drive the car. When he/she presses the front / the back/the left/the right on the LCD screen of the phones, the car can move forward / backward / the left or / the right. In addition, the gravity sensing of the smart telephone can also control the motion of the car wirelessly in the same way. The car itself can avoid the obstacle intelligently. The ultrasonic sensor can finish the rotation of the 180 degrees to detect the obstacle with the help of the steering gear. And the system also designed the PCB and made the hardware by ourself. The system has advantages of low-cost, convenience and feasibility. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3743